ตัวชี้วัดความสำเร็จเกษตรพอเพียงของปราชญ์ชาวบ้านและพหุภาคีภาคอีสาน - เพ็งพินิจ และคณะ, ธวัชชัย (Journal of Multidisciplinary in Social Sciences, 2013)
บทคัดย่อ การวิจัยครั้งนี้ใช้ระเบียบวิธีวิจัยเชิงคุณภาพ เพื่อศึกษาปัญหาในการทำการเกษตรกรรมและตัวชี้วัดความสำเร็จเกษตรพอเพียงของปราชญ์ชาวบ้านและพหุภาคีภาคอีสาน 12 เครือข่าย ด้วยการสังเกตแบบมีส่วนร่วม สัมภาษณ์เชิงลึก สนทนากลุ่ม และประชุมเชิงปฏิบัติการ ใช้เวลา 12 เดือน จากการวิจัย พบว่า ปัญหาในการทำการเกษตรกรรมแบ่งออกเป็น 4 ด้าน ประกอบด้วย 1) ปัญหาภายใน ได้แก่ สุขภาพไม่แข็งแรง ขาดแรงงาน/ไม่มีผู้สืบทอดงาน ขาดความรู้และประสบการณ์ ไม่มีเงินทุน หนี้สิน รายรับรายจ่ายไม่สมดุล ครอบครัวแตกแยก 2) ปัญหาภายนอก ได้แก่ ราคาผลผลิตตกต่ำ สารพิษตกค้าง โรคระบาด ขาดตลาดรองรับผลผลิต ขาดการสนับสนุนจากภายนอก ค่าครองชีพสูง สัตว์เลี้ยงทำลายพืชผล 3) ปัญหาจากธรรมชาติ ได้แก่ ภัยแล้ง แมลงศัตรูพืช น้ำท่วม ดินขาดความอุดมสมบูรณ์ และ 4) ปัญหาด้านปัจจัยการผลิต ได้แก่ ไม่มีแหล่งน้ำ ต้นทุนการผลิตสูง ขาดพันธุ์พืชที่หลากหลาย ขาดเครื่องมือในการทำเกษตร ไม่มีที่ดินทำกิน ค่าแรงงานแพง ตัวชี้วัดความสำเร็จเกษตรพอเพียงของปราชญ์ชาวบ้านและพหุภาคีภาคอีสาน แบ่งออกตามหลักปรัชญาเศรษฐกิจพอเพียงใน 7 องค์ประกอบ ดังนี้ ทางสายกลางมี 9 ตัวชี้วัดประกอบด้วย ลดรายจ่าย ทำเกษตรผสมผสาน ไม่สร้างหนี้ ไม่เบียดเบียน พอใจในสิ่งที่ตนมี เอาความสุขตั้ง ทำตามกำลัง ยึดหลักธรรม และหางานเสริมเพิ่มรายได้ ความพอประมาณมี 8 ตัวชี้วัดประกอบด้วย พอใจในสิ่งที่ตนมี พอกินพออยู่พอใช้ ทำจากน้อยไปหามาก รู้จักตนเอง พึ่งตนเอง ทำตามกำลัง ไม่ตามกระแส และไม่เดือดร้อนหรือสบายเกินไป ความมีเหตุผลมี 13 ตัวชี้วัดประกอบด้วย ไม่เห็นแก่ตัว รับฟังความคิดคนอื่น วางแผนการทำงาน ไว้เนื้อเชื่อใจ เรียนรู้ แลกเปลี่ยนความคิดเห็น ทำตามกำลัง เป็นผู้นำและผู้ตามที่ดี วิเคราะห์ข้อดีข้อเสียของงาน เสียสละ ยึดหลักธรรม ไม่ใจร้อน และทำจากน้อยไปหามาก การมีภูมิคุ้มกันในตัวที่ดีมี 13 ตัวชี้วัดประกอบด้วย ปลูกทุกอย่างที่กินกินทุกอย่างที่ปลูก ครอบครัวอบอุ่น ลดรายจ่าย ไม่ตามกระแส ปลูกไม้ผลไม้ยืนต้นและสมุนไพร ร่างกายแข็งแรง พอกินพออยู่พอใช้ มีลูกหลานสืบทอด สามัคคี แลกเปลี่ยนความคิดเห็น ชุมชนเข้มแข็ง รวมกลุ่มทำกิจกรรมร่วมกัน และมีเงินออม เงื่อนไขความรู้มี 9 ตัวชี้วัดประกอบด้วย ลดรายจ่าย เรียนรู้ รวมกลุ่มทำกิจกรรมร่วมกัน พอใจในสิ่งที่ตนมี ทำตามกำลัง ไม่สร้างหนี้ ครอบครัวอบอุ่น ปลูกทุกอย่างที่กินกินทุกอย่างที่ปลูก และทำบัญชีครอบครัว เงื่อนไขคุณธรรมมี 12 ตัวชี้วัดประกอบด้วย ซื่อสัตย์ เอื้ออาทร ช่วยเหลือกัน รู้จักตนเอง เลิกอบายมุข รวมกลุ่มทำกิจกรรมร่วมกัน รับฟังความคิดคนอื่น เหลือกินแจก แลกเปลี่ยนความคิดเห็น ยึดหลักธรรม สามัคคี และรักษาสืบทอดประเพณี ความสมดุล มั่นคง ยั่งยืนมี 11 ตัวชี้วัดประกอบด้วย สิ่งแวดล้อมดี พอกินพออยู่พอใช้ ยั่งยืนชั่วลูกหลาน ยึดหลักธรรม เอื้ออาทร ไม่เบียดเบียน พึ่งตนเอง ช่วยเหลือกัน รับฟังความคิดคนอื่น ซื่อสัตย์ และสามัคคี เมื่อนำทุกตัวชี้วัดมาเปรียบเทียบใน 7 องค์ประกอบของปรัชญาเศรษฐกิจพอเพียง จะมีตัวชี้วัดรวมทั้งสิ้น 43 ตัวชี้วัด แบ่งออกเป็น ตัวชี้วัดที่ปรากฏอยู่ 4 องค์ประกอบ มี 2 ตัวชี้วัด ปรากฏอยู่ 3 องค์ประกอบ มี 7 ตัวชี้วัด ปรากฏอยู่ 2 องค์ประกอบ มี 12 ตัวชี้วัด และปรากฏอยู่ 1 องค์ประกอบ มี 22 ตัวชี้วัด คำสำคัญ: ตัวชี้วัด เกษตรพอเพียง เศรษฐกิจพอเพียง ปราชญ์ชาวบ้าน Abstract This research using the methodology of qualitative research aimed to study the problems of farming and success indicators of sufficient farming of local philosophers and multilateral in the Northeast covering 12 networks. The research instruments used in collecting data were participant observation, in-depth interviews, focus group and workshop in the duration among 12 months. The findings of the study were as follows: Problems of farming were divided into four areas include: 1) An internal problems are health is not strong, lack of labor/no succession, lack of knowledge and experience, no capital, debt, revenue expenditure imbalance and family disputes. 2) An external problems are product low prices, pesticide residues, disease in plants, production support in short supply, lack of support from the outside, high cost of living and animals destroyed crops. 3) The problems of natures are drought, insect pests, flood and lack of soil fertility. 4) Problems of production factors are no water source, high production costs, lack of plant variety, lack of farming tools, no land and expensive labor costs. Success indicators of sufficient farming of local philosophers and multilateral in the Northeast. The Sufficiency Economy Philosophy was seven elements. Middle path were nine indicators include reducing expenses, mixed farming, not create a debt, not encroach, satisfied with what they have, set out happy, follow the power, based on principles and jobs extra income. Moderation were eight indicators include satisfied with what they have, fair enough is enough to eat, made from ascending, known self, self-reliance, follow the power, not the flows and no trouble or too comfortable. Reasonableness were 13 indicators include unselfish, listen to others ideas, planning work, trust, learning, exchange of ideas, follow the power, a good leader and a follower, analyze the merit and flaw of the job, sacrifice, based on principles, not impatient and made from ascending. Self-immunity were 13 indicators include planted everything eat everything planted, a happy family, reduce expenses, not the flows, planting fruit trees and herbal, health, fair enough is enough to eat, the progeny inherit, unity, exchange of ideas, strong community, group activities together and have savings. Conditions of knowledge were nine indicators include reduce expenses, learning, group activities together, satisfied with what they have, follow the power, not create a debt, a happy family, planted everything eat everything planted and accounting family. Conditions of morality were 12 indicators include honest, thoughtfulness, help each other, known self, out obriamuk, group activities together, listen to others ideas, surplus to eat free, exchange of ideas, based on principles, unity, and treatment of inherited traditions. Balance and sustainability were 11 indicators include environmental good, fair enough is enough to eat, sustainable evil offspring, based on principles, thoughtfulness, do not encroach, self-reliance, help each other, listen to others ideas, honest and unity. All indicators were compared with seven elements of the sufficiency economy philosophy was totally 43 indicators which divided into two indicators with four elements seven indicators with three elements 12 indicators with two elements and 22 indicators with one element.ฟัง Key word: Indicators, Sufficient farming, Sufficiency economy, Local philosopher